2016
DOI: 10.1111/jphp.12520
|View full text |Cite
|
Sign up to set email alerts
|

Thymol accelerates the recovery of the skeletal muscle of mice injured with cardiotoxin

Abstract: This study suggests that thymol ameliorates inflammatory response and accelerates regeneration in cardiotoxin-induced muscle injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In addition, thymol is able to promote complete replacement of type III to type I collagen in 14 days, indicating a normal, dynamic collagenation as previously reported in other experimental wound healing studies with red propolis and usnic acid . These findings are reported by other studies with thymol and carvacrol, which demonstrate that both isomers stimulate the production of collagen . Therefore, the discoveries mentioned suggest that these monoterpenes may play an important modulating effect on fibroblast metabolism and collagen synthesis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, thymol is able to promote complete replacement of type III to type I collagen in 14 days, indicating a normal, dynamic collagenation as previously reported in other experimental wound healing studies with red propolis and usnic acid . These findings are reported by other studies with thymol and carvacrol, which demonstrate that both isomers stimulate the production of collagen . Therefore, the discoveries mentioned suggest that these monoterpenes may play an important modulating effect on fibroblast metabolism and collagen synthesis.…”
Section: Discussionsupporting
confidence: 83%
“…[51,52] These findings are reported by other studies with thymol and carvacrol, which demonstrate that both isomers stimulate the production of collagen. [53,54] Therefore, the discoveries mentioned suggest that these monoterpenes may play an important modulating effect on fibroblast metabolism and collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…But, thymol possesses a more superior effect than its isomer carvacrol in the same model and the actions are attributed to the antioxidant, anti-inflammatory, and antiapoptotic activity of thymol (El-Sayed et al, 2016). A report from Cardoso et al (2016) has revealed that thymol (10–100 mg/kg) attenuates inflammation and recovers skeletal muscle from cardiotoxicity in mice.…”
Section: Thymol In Cardiometabolic Diseasesmentioning
confidence: 99%
“…Fourteen days after CTX injection into the TA muscle, exogenous Ang-1 significantly increased muscle contractility, fiber regeneration, and capillary density [15]. Antiinflammatory compounds such as thymol were found to accelerate skeletal muscle regeneration by observing a reduction in the number of mast cells and a decrease in the final percent of collagen after CTX injection into the gastrocnemius muscle [16]. However, while myotoxin injection is an ideal Figure 1.…”
Section: Myotoxinsmentioning
confidence: 99%
“…Fourteen days after CTX injection into the TA muscle, exogenous Ang-1 significantly increased muscle contractility, fiber regeneration, and capillary density [ 15 ]. Anti-inflammatory compounds such as thymol were found to accelerate skeletal muscle regeneration by observing a reduction in the number of mast cells and a decrease in the final percent of collagen after CTX injection into the gastrocnemius muscle [ 16 ]. However, while myotoxin injection is an ideal model to understand the underlying mechanisms of skeletal muscle regeneration, it is unable to model the frank loss of tissue that occurs in traumatic injury, such as those presenting from VML, limiting its relevance for clinical injuries.…”
Section: Myotoxinsmentioning
confidence: 99%